Family succession in rural properties (Research, Society and Development, 2020)
The theme of family succession becomes relevant in the study of the management of rural properties, since many family properties are experiencing the succession process and are often unaware of how to proceed with the transmission of property management to a successor. The objective of the study was to describe how the managers of the rural properties are carrying out the family succession process. As a research problem, did we try to answer how rural property managers are working on the family succession process? Regarding the methodology, the deductive, qualitative and quantitative approach methods were adopted. The procedures used were descriptive and field research. Data collection took place through observation, interview, questionnaire, bibliographic research and documentary research. For data analysis, an electronic spreadsheet and content analysis were used. The theoretical foundation was composed of previous studies related to the theme. Through bibliographic research, the elements that characterize family succession were sought; and the characteristics of rural properties by size criteria. The study was developed in 2020, encompassing 18 rural properties in the municipality of Alegria - RS. As the main results of the study, it was evidenced that it is essential for the managers of the rural properties to have knowledge about the family succession, because the lack of a succession process can result in the rupture of the family business, and planning it correctly will allow the continuity of business. It is noteworthy that 61,11% of managers do not prepare the succession. It was found that most parents encourage their children to remain living and working on the rural property.